Selection Wages: An Illustration - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
Offering higher wages may enable firms to attract more applicants and screen them more carefully. If firms compete in this way in the labor market, "selection wages" emerge. This note illustrates this wage-setting mechanism. Selection wages may engender unconventional results, such as a pre-tax wage compression induced by the introduction of a progressive wage tax.
urn:nbn:de:bvb:19-epub-958-8
Keywords: J31; J41; J62; J63; 330; wage formation; efficiency wage; incentive wage; mobility; job-specific pay; wage-tax; Arbeitsnachfrage; Lohntheorie; Theorie